The Benefits of Acupuncture in Treating Anxiety - Franco, Leonardo Ricardo (2019)
Anyone can go through anxiety disorder, it is an evil that reaches all social classes, it presents itself before important events, business presentations, when we are being analyzed. Unfortunately when untreated these symptoms can become a negative anomaly, such as fears, and can become chronic. When the anxiety victim goes into chronic condition, they may be plagued by panic attacks, obsessive thoughts, flashbacks of traumatic events, nightmares, or various physical symptoms of fear. There are adequate and effective treatments that can cure this problem, acupuncture, traditional Chinese medicine, which has been used as a supplement to allopathic medicine, through needles is an allied to the treatment of anxiety. Based on this premise, the present bibliographical article aims to attest that acupuncture helps in the treatment of anxiety. In this way, research was done on scientific articles and theses related to the proposed theme.